2005
DOI: 10.1161/01.cir.0000157736.19739.d0
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Stroke Subtype Incidence Among Whites, Blacks, and Hispanics

Abstract: Background-Stroke incidence is greater in blacks than in whites; data on Hispanics are limited. Comparing subtype-specific ischemic stroke incidence rates may help to explain race-ethnic differences in stroke risk. The aim of this population-based study was to determine ischemic stroke subtype incidence rates for whites, blacks, and Hispanics living in one community. Methods and Results-A comprehensive stroke surveillance system incorporating multiple overlapping strategies was used to identify all cases of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
478
6
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 694 publications
(521 citation statements)
references
References 34 publications
21
478
6
8
Order By: Relevance
“…Our findings are consistent with prior studies demonstrating higher AIS hospitalizations in blacks and Hispanics compared to whites 6, 8, 9, 10, 29. AIS hospitalization rates were greatest in blacks throughout the decade, and in 2010 were more than double the hospitalization rates of both whites and Hispanics.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with prior studies demonstrating higher AIS hospitalizations in blacks and Hispanics compared to whites 6, 8, 9, 10, 29. AIS hospitalization rates were greatest in blacks throughout the decade, and in 2010 were more than double the hospitalization rates of both whites and Hispanics.…”
Section: Discussionsupporting
confidence: 93%
“…AIS rates were 2‐fold greater in young black versus white women and men in Baltimore County,29 higher in blacks compared to whites in the Greater Cincinnati/Northern Kentucky Stroke Study,6 and higher in Mexican Americans compared to non‐Hispanic whites in the Brain Attack Surveillance in Corpus Christi Project 10. Data from the Northern Manhattan Stroke Study showed that the annual incidence of first AIS from 1993 to 1997 was greatest in blacks, followed by Hispanics (mainly of Caribbean origin) and whites 8. The age‐adjusted AIS hospitalization rates in Florida for individuals aged 25 to 49 years was greatest in blacks, followed by whites, then Hispanics (mainly Cuban, Puerto Rican, Mexican, and South Americans in origin) regardless of sex 9…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disparities exist in stroke mortality, morbidity, prevalence of biological and environmental risk factors, healthcare access, and quality of care. Incidence data from NOMAS (the Northern Manhattan Study) has demonstrated racial‐ethnic differences in stroke incidence, with blacks and Hispanics having more than a 2‐fold increase in annual stroke incidence compared with whites 4, 5. Some studies have documented disparities in access to acute stroke care, activation of 911 services, delayed arrival to the emergency department, longer waiting times, and treatment delays in thrombolysis 3.…”
Section: Introductionmentioning
confidence: 99%